ANALISIS PERILAKU SOSIAL EMOSIONAL MAHASISWA PGSD SAAT PEMBELAJARAN DALAM JARINGAN - Arya Setya Nugroho (LP4MK STKIP PGRI Lubuklinggau, 2022)
The covid pandemic period still lingers and causes learning to be carried out online even though 20% - 50% of the total number of planned meetings. Online learning also has an impact on the development of student behavior, such as emotional social attitudes. This study aims to determine the impact of online learning on social emotional attitudes that arise in students. This research uses descriptive qualitative method by applying driven theory technique. Data was collected by means of interviews with students. The results obtained, online learning raises students' emotional social attitudes, namely the lack of socialization between students with one another; each student's emotions tend to feel bored during online lectures; and students are less disciplined. It is hoped that this research can provide an overview of the preparation and planning of online lectures.